2014
DOI: 10.1521/aeap.2014.26.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Finding and Recruiting the Highest Risk HIV-Negative Men Who Have Sex With Men

Abstract: This study compared the ability of different field and online recruitment venues to reach those at highest risk for HIV infection among HIV-negative men who have sex with men (MSM), given that some subgroups are difficult to reach, and venues vary in the demographic characteristics of the samples they yield. Compared to other venues, dating/hookup websites reached significantly higher-than-expected concentrations of White MSM aged 40 and above, including those who reported unprotected anal intercourse (UAI). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…Recruitment of HIV-positive MSM presents unique challenges, but also the possibility of recruiting in venues that are typically not included in strategies aimed at reaching HIV-negative MSM (e.g., ASOs). The present analyses will provide a more nuanced understanding of the efficiency of different recruitment venues in reaching self-identified HIV-positive MSM, thus expanding on Parsons et al (2013) and complementing the findings by Vial et al (2014).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Recruitment of HIV-positive MSM presents unique challenges, but also the possibility of recruiting in venues that are typically not included in strategies aimed at reaching HIV-negative MSM (e.g., ASOs). The present analyses will provide a more nuanced understanding of the efficiency of different recruitment venues in reaching self-identified HIV-positive MSM, thus expanding on Parsons et al (2013) and complementing the findings by Vial et al (2014).…”
mentioning
confidence: 76%
“…This is particularly true with regards to specific subgroups of HIV-positive MSM who tend to be underrepresented relative to their HIV prevalence, such as racial/ethnic minorities (Du Bois, Johnson, & Mustanski, 2012). Because different recruitment strategies vary in the characteristics of the samples they yield (Fisher, Purcell, Hoff, Parsons, & O’Leary, 2006; Grov, 2012; Parsons et al, 2013; Vial, Starks, & Parsons, 2014), knowing where to concentrate efforts can maximize the likelihood of reaching specific subgroups of HIV-positive MSM. However, despite the potential utility of this information, few studies report associations among recruitment venue and risk behaviors or HIV prevalence (Barresi et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Internet samples of MSM, compared to those recruited through conventional sampling (e.g., face-to-face and snowball sampling), are more likely to identify as bisexual, have sex with women (MSMW), and engage in high-risk sexual behavior [25, 26] and MSMW are less likely to have been exposed to AIDS prevention interventions [27]. Rates of unprotected anal intercourse (UAI) in the past 3 months have also been found to be high among MSM who use Grindr [28, 29] and MSM recruited online report higher rates of UAI than MSM recruited at clubs or bars and in community venues [30]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a database search revealed few studies that have explored the use of Facebook (Bull et al, 2011). The studies using Facebook have focused on topics, such as sexual health, HIV education, influence of religion on behaviors, recruitment strategies, and social networks (Bull et al, 2011; Bull, Levine, Black, Schmiege, & Santelli, 2012; Hunter et al, 2014; Vial, Starks, & Parsons, 2014; Washington, Patel, & Meyer-Adams, 2015; Young, Dutta, & Dommety, 2009; Young, Holloway, et al, 2014; Young & Jordan, 2013; Young, Shakiba, Kwok, & Montazeri, 2014). No studies were revealed that aimed to deliver a motivational video intervention to increase HIV testing uptake among young BMSM with preintervention and postintervention assessment of risk behaviors and HIV testing uptake.…”
mentioning
confidence: 99%